IMPLEMENTATION OF CIVIL SERVANT DISCIPLINE REGULATIONS AT THE MINISTRY OF RELIGIOUS AFFAIRS OFFICE IN LHOKSEUMAWE CITY - Muti, Sarini; A. Rahman, Dahlan; Fazil, Muhammad (FISIP Universitas Malikussaleh, 2025)
The Office of the Ministry of Religious Affairs of Lhokseumawe City still has not implemented Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. It can be seen that there are still some ASN employees who do not obey discipline in accordance with the applicable PP. This thesis discusses the Implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Office of the Ministry of Religion of Lhokseumawe City in 2022-2023 using Merilee S. Grindle's theory which is measured from the process of achieving outcomes (i.e. whether or not the goals to be achieved are achieved) The type of research used is qualitative descriptive with data collection techniques in the form of interviews, documentation and observations. The sampling technique was carried out by purposive sampling. The data source uses primary data, secondary data. Data analysis techniques with data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Office of the Ministry of Religion of Lhokseumawe City is optimal, but there are obstacles to the work culture that are difficult to change and there are still low sanctions so that the perpetrators of disciplinary violations have not been deterred. The recommendation of the Office of the Ministry of Religion of Lhokseumawe City is that it is necessary to carry out regular socialization so that employees can understand the content of the policy of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline.